Analysis On The Influence of Product and Service Development To Customer Satisfaction - Puspitaningsih, Ratna; Saphiranti, Dona (The Indonesian Journal of Business Administration, 2013)
Nowadays there are many shoes especially woman’s shoes are sold in the market. Woman’s shoes sold in a variety of variants in term of prices, models, colors, function, size, and product quality. Based on the eight brands of local designers, Yongki Komaladi is the local brand that is used for comparison to KittyCats. Yongki Komaladi is chosen because it has similarities in the variety of its product variants which sell all types of shoes and the existence of Yongki Komaladi is already well known by the public. KittyCats needs attributes data on customers satisfaction of the shoes that will be implemented to KittyCats products. To receive these data, it needs survey of the customer satisfaction in women’s shoe products. Based on the results of multiple regression analysis, the independent variables that have the most influences effect to the dependent variable is the X1 (product excellence) variable with a coefficient of 0.302. In the other hand, based on the calculation of percentage of index number on those all three variables, product excellence and customer satisfaction are mostly located in the high category between 70.01 - 100.00. Based on multiple regression analysis and percentage of index number, the root of most problems which affecting the level of customer satisfaction is product excellence. The business solution alternatives are based on the root problems that occur in Yongki Komaladi. So variable product excellence becomes a priority that must be corrected before the variable service excellence. Based on the recommended alternative solutions, this research focused on product excellence variables with the highest priority by taking three solutions alternative from each indicator with the highest percentage value index numbers. The implementation plan for KittyCats is done based on priority of alternative solutions of each  indicators.  The implementation plan are size excellence (the right size, size in accordance with the national standard, and size bigger than 35), durability excellence (shoes that not easily damage, good quality material, and resist for all condition), comfort excellence (not blisters, soft and tender, and convenient to use in a long time), and model excellence (elegant, up to date, and simple model). Key Words: KittyCats, product excellence, service excellence, customer satisfaction